Step
*
1
1
1
of Lemma
strong-continuity2-implies-uniform-continuity
1. F : (ℕ ⟶ 𝔹) ⟶ 𝔹
2. ∃M:n:ℕ ⟶ (ℕn ⟶ 𝔹) ⟶ (𝔹?)
    ∀f:ℕ ⟶ 𝔹. ((∃n:ℕ. ((M n f) = (inl (F f)) ∈ (𝔹?))) ∧ (∀n:ℕ. (M n f) = (inl (F f)) ∈ (𝔹?) supposing ↑isl(M n f)))
⊢ ∃M:n:ℕ ⟶ (ℕn ⟶ 𝔹) ⟶ (𝔹?) [(∀f:ℕ ⟶ 𝔹
                                  ((∃n:ℕ. ((M n f) = (inl (F f)) ∈ (𝔹?)))
                                  ∧ (∀n:ℕ. (M n f) = (inl (F f)) ∈ (𝔹?) supposing ↑isl(M n f))))]
BY
{ ParallelLast }
Latex:
Latex:
1.  F  :  (\mBbbN{}  {}\mrightarrow{}  \mBbbB{})  {}\mrightarrow{}  \mBbbB{}
2.  \mexists{}M:n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbB{})  {}\mrightarrow{}  (\mBbbB{}?)
        \mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbB{}
            ((\mexists{}n:\mBbbN{}.  ((M  n  f)  =  (inl  (F  f))))  \mwedge{}  (\mforall{}n:\mBbbN{}.  (M  n  f)  =  (inl  (F  f))  supposing  \muparrow{}isl(M  n  f)))
\mvdash{}  \mexists{}M:n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbB{})  {}\mrightarrow{}  (\mBbbB{}?)  [(\mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbB{}
                                                                    ((\mexists{}n:\mBbbN{}.  ((M  n  f)  =  (inl  (F  f))))
                                                                    \mwedge{}  (\mforall{}n:\mBbbN{}.  (M  n  f)  =  (inl  (F  f))  supposing  \muparrow{}isl(M  n  f))))]
By
Latex:
ParallelLast
Home
Index